A Review of Research Frontiers and Advances in Continental Sequence Stratigraphy - Guo, Fuqiang (International Journal of Natural Resources and Environmental Studies, 2026)
Sequence stratigraphy not only provides an isochronous stratigraphic framework for basin analysis, but also offers an important integrated geological framework for sedimentary paleogeographic reconstruction and the exploration and development of sedimentary mineral resources. Over the past three decades, sequence stratigraphy has continued to develop in terms of theoretical systems, sequence architecture, integrated interpretation of multiple datasets, and applications in energy exploration. Significant progress has been made particularly in the controlling factors of sequence formation in continental basins, sequence-stratigraphic architecture of faulted, depressed, and foreland lacustrine basins, the distribution patterns of sand bodies, and research methods for sequence stratigraphy in continental lacustrine basins. Compared with marine basins, continental lacustrine basins are jointly controlled by tectonic activity, climatic change, lake-level fluctuation, proximal and multiple sediment supplies, and rapid changes in sedimentary facies; therefore, their sequence composition and stratigraphic stacking patterns are more complex. Future research on continental sequence stratigraphy should further focus on sequence architecture in different types of basins, standardization of research terminology and workflows, relationships between sequences and source-to-sink systems, relationships between sequences and shoreline-migration trajectories, stratigraphic stacking patterns and sedimentary responses, deep-water sequence stratigraphy, and numerical simulation of sequence architecture, so as to better serve the exploration and development of energy resources.